Implementation of an E-Module on The Diversity of Living Things to Enhance Critical Thinking Skills and Learning Independence - Nuryunita Dewantari; Ayu Lestari (Indonesian Journal of Science and Education, 2024)
Critical thinking is important because it enables individuals to analyze information objectively, make well-reasoned decisions, and solve problems effectively. But, it is a decline in international learning outcomes due to the pandemic. The aim of this research is to analyze the effect of using an e-module on the diversity of living things to enhance students' critical thinking skills and learning independence. The research design used was quasi-experimental with a nonequivalent control group design. Two groups with a total of 74 students were selected for this study using purposive sampling. The instruments used in this research included a written test to assess critical thinking skills and a questionnaire to evaluate learning independence. The data analysis conducted included an independent samples t-test and an n-gain test. Based on the results of an independent samples t-test, there is a significant difference between the two groups in students' critical thinking skills and learning independence. N-gain tests also support these findings, with critical thinking skills scores of 0.60 in the experimental class and 0.57 in the control class. Additionally, learning independence scores were 0.78 for the experimental class and 0.36 for the control class. It can be concluded that there is a significant positive effect of using the e-module on the diversity of living things to enhance students' critical thinking skills and learning independence.